The role of gibberellin in wheat grain development - Wanchoo-Kohli, Aakriti (2017)
The plant hormone gibberellin (GA) is known to influence grain size and flour quality, flowering, development and germination in wheat. GA also induces the production of α-amylase by the aleurone layer and premature production of this enzyme during development results in degraded starch in the mature grain. While GA is proposed to have a negative effect on flour quality, it is essential for early grain development and these effects are separated both temporarily and spatially in the grain. It was the aim of this project to further understand the role GA plays in wheat grain development and in order to achieve this constructs were designed to alter GA metabolism or signalling in the seed-coat, endosperm, embryo or aleurone of developing wheat grains. In plants where GA content was manipulated in the developing endosperm it was shown that GA produced by this tissue is involved in regulating grain size and morphology. This was demonstrated by the differences observed between the transgenics and their nulls in grain size, hardness index and moisture content. Additionally, in these lines no differences were observed in the α-amylase levels, implying that GA produced by the endosperm might not be influencing the production of this enzyme. However, GA insensitivity introduced in the embryo and aleurone layers did not display the hypothesised phenotypes and was inconclusive in determining the role of GA signalling in grain development. During this project a reliable qPCR based method using TaqMan assays was also developed to determine zygosity of transgenic plants in the T1 generation. This method was successful in reducing the number of generations required to select homozygous material compared to more conventional methods.